Modeling and Verification of Kinematics Error of 3UPS-PU Parallel Mechanism - Wang Na; Zhang Tao; Wang Qiuhong (Jixie chuandong, 2020)
Taking the 3UPS-PU parallel mechanism，the experiment platform of sample package special test in the lunar exploration project as the study object，the error analysis model of 3UPS-PU parallel mechanism is established by using matrix differential method，which verified the correctness of the error analysis model from the macro to micro accordance with the volume error and single element of the pose error. And based on the results of single error analysis through the error model，the main error terms are analyzed，which could afford the reliable foundations for selection of parts manufacturing tolerances and its assembly levels. The method can not only solve a range of issues related to error analysis of 3UPS-PU parallel mechanism，but also apply to research and analysis of similar mechanism.